The Counseling Needs of female Gifted Students in Asir Region According to the Vision of the Kingdom 2030: A Proposal Counseling plan for Gifted students - Arnaout, Boshra Ismail Ahmed; Al Qadmi, Fatima Yahya Hassan; Al Maadi, Khadija Abboud (Journal of Educational and Psychological Sciences, 2019)
This study aimed to determine counseling needs of female gifted students in the Asir region, as well as to identify the differences in the level of needs among female gifted students due to the school stage, and develop a proposed counseling plan. The researchers selected a random sample of (339) female gifted students in middle and high school for the academic year 1439/1440 AH, who were classified as gifted according to the classification of the Ministry of Education in the Kingdom of Saudi Arabia, their ages ranging between (13-18) years. The number of female gifted students at Middle schools in the research sample were 163 students (48%) their ages ranged between 13-15 years with an average age of 13.97 year and a standard deviation of 0.765, but the number of female gifted students in the secondary schools of the study sample was (176) students (52%), their ages ranging between (16-18) years, with an average age of 17.06 year and a standard deviation of (0.886). The researchers applied the scale of counseling needs of gifted students(prepared by the researchers) on them. The results showed that the total score of counseling needs, educational counseling needs, psychological and social counseling needs of gifted students from the middle schools were high (76.895, 39.184, 37.716) respectively, and the total score of counseling needs, educational needs, psychological and social needs were also high among female gifted students at the secondary schools (77.364, 36.369, 40, 994) respectively. The results showed statistically significant differences at the level of (0.01) among the average scores of the educational counseling needs due to the school stage, the differences were in favor of female gifted students in the middle schools (t = 5.621), which was the highest educational counseling needs (t =7.923), while the differences in the total score of the counseling needs among middle and secondary schools female gifted students were not significant. score in the middle and secondary schools were not significant (t = 0.594). The results have been interpreted in light of the theoretical framework and previous studies. A number of recommendations and a counseling plan for gifted students at the middle and secondary schools have also been proposed as a guide for gifted student counselors.
Keywords: Counseling needs; student counsellor; suggested counseling plan; gifted people